GAMBARAN RELIGIUSITAS PADA LANSIA DI GRIYA PMI MOJOSONGO (Lembaga Pengembangan Kinerja Dosen, 2023)
Generally, older individuals are typically referred to as individuals who are 65 years old and older. Aging is a natural progression in the human lifespan, often characterized by a decline in physical abilities. Every elderly person yearns for a peaceful and contented life, and one way to fulfill this psychological need is by enhancing their faith and devotion. The objective of this study is to assess the religious inclination of the elderly residing in Griya PMI. The researchers employed a qualitative approach, conducting semi-structured interviews and observations with a total of seven elderly participants. The findings of this study indicate that, on average, the subjects displayed a commendable level of religiosity.